2012
DOI: 10.1016/j.compositesb.2012.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study about heating systems for pultrusion process

Abstract: Different heating systems have been used in pultrusion, where the most widely used heaters are planar resistances. The primary objective of this study was to develop an improved heating system and compare its performance with that of a system with planar resistances. In this study, thermography was used to better understand the temperature profile along the die. Finite element analysis was performed to deter-mine the amount of energy consumed by the heating systems. Improvements were made to the die to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…A previous research study conducted by the present authors, Silva et al [26] also showed a significant reduction on energy consumption that could be obtained using embedded cylindrical heaters into the die instead of external planar resistances. It was found that embedded resistances significantly enhance the energetic performance of pultrusion process, leading to 57% decrease of energy consumption exclusively due to die heating system.…”
Section: Energy Savings On Pultrusion Manufacturing Processesmentioning
confidence: 93%
“…A previous research study conducted by the present authors, Silva et al [26] also showed a significant reduction on energy consumption that could be obtained using embedded cylindrical heaters into the die instead of external planar resistances. It was found that embedded resistances significantly enhance the energetic performance of pultrusion process, leading to 57% decrease of energy consumption exclusively due to die heating system.…”
Section: Energy Savings On Pultrusion Manufacturing Processesmentioning
confidence: 93%
“…Moreover, in posterior studies, it was also found that the optimized position of the internal heaters throughout the die could even additionally reduce the energy consumption linked to the heating process 8% more [53]. More details of conducted research studies can be found in Silva et al [52,53].…”
mentioning
confidence: 98%
“…Earlier studies conducted by the authors showed that significant savings on energy consumption of the pultrusion process could be achieved using embedded cylindrical heaters into the die instead of external planar resistances [52]. Experiments were conducted in a 900 mm length die during the manufacturing process of a standard pultrusion profile (Profile U: 50 × 10 × 4), keeping all the other process parameters constant-pulling speed, pulling force, total resistance power and temperature profile (TP)-along the die.…”
mentioning
confidence: 99%
“…Obtained results showed that internal resistances enhance significantly the energetic performance of pultrusion process, leading to 57% decrease of energy dispend in heating process, which represents a reduction of 17% of total energy consumed. A detailed explanation of conducted research study can be found in Silva et al [7].…”
Section: Re-engineering Manufacturing Process In Order To Maximize Enmentioning
confidence: 99%